2022
DOI: 10.1029/2022gb007635
|View full text |Cite
|
Sign up to set email alerts
|

Recent Seasonal Variations in Ecosystem Water Use Efficiency in China's Key Tropical‐Subtropical Transitional Zones in Response to Climate Change

Abstract: Understanding the response of terrestrial ecosystem water use efficiency (WUE) to climate change is critical to accurately represent the carbon‐water cycle processes. However, how WUE dynamics are evolving under seasonal climate variations and biome‐specific characteristics remains still unclear. In this study, we integrated two state‐of‐the‐art retrieval algorithms to estimate gross primary productivity (GPP) and evapotranspiration (ET) from satellite MODIS records. Such metrics served as input to quantify ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 113 publications
0
0
0
Order By: Relevance
“…MODIS‐based NDVI 16‐day products (MOD13Q1) with a spatial resolution of 250 m. While GPP 8 days (MOD17A2) available with a spatial resolution of 500 m, and ET of 8 days (MOD16A2) with a spatial resolution of 500 m was taken from (https://www.earthdata.nasa.gov/) as shown in Table 1. ET and GPP were developed using the Penman‐Moneith equation and light use efficiency model (Liu et al, 2022). All these datasets were downloaded using the MODIS library and packages in R software version R i386 4.0.3 from 2001 to 2022 (https://cran.r-project.org/bin/windows/base/) (Baig et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MODIS‐based NDVI 16‐day products (MOD13Q1) with a spatial resolution of 250 m. While GPP 8 days (MOD17A2) available with a spatial resolution of 500 m, and ET of 8 days (MOD16A2) with a spatial resolution of 500 m was taken from (https://www.earthdata.nasa.gov/) as shown in Table 1. ET and GPP were developed using the Penman‐Moneith equation and light use efficiency model (Liu et al, 2022). All these datasets were downloaded using the MODIS library and packages in R software version R i386 4.0.3 from 2001 to 2022 (https://cran.r-project.org/bin/windows/base/) (Baig et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…WUE is the ratio of biomass by plants or crops to the amount of water consumed. WUE also refers to measuring the interchange between water loss and the increase of carbon in terrestrial ecosystems, as shown in equation (Liu et al, 2022; Qin et al, 2023). italicWUEgoodbreak=GPPET.$$ WUE=\frac{GPP}{ET}.…”
Section: Methodsmentioning
confidence: 99%
“…The coupled product can effectively avoid internal inconsistencies between ET and GPP from the uncoupled product and therefore could provide higher-accuracy eWUE estimates [13]. Over the years, a large amount of eWUE-related research (e.g., the spatial and temporal variation of eWUE, the response of eWUE to drought and natural and human activities, and the driver of eWUE changes [1,[39][40][41][42][43][44][45][46][47][48]) has been conducted for various PFTs (including but not limited to cropland); however, most of these studies calculated eWUE based on the MODIS product, whose accuracy is strongly queried by this study as well as previous studies [2,13,49]. This study indicates that the coupled product is more suitable and effective to be applied in the eWUE-related research for different crop species to reduce the uncertainty from the inaccurate RS-based eWUE estimates from the uncoupled products.…”
Section: Implications and Future Workmentioning
confidence: 99%
“…Ecosystem water use efficiency (eWUE), the ratio of gross primary production (GPP, the total amount of carbon fixation by vegetation through photosynthesis) and evapotran-spiration (ET, the sum of evaporation from soil and transpiration through plant leaves), is a critical indicator connecting the terrestrial carbon and water cycles and reflecting multiple ecosystem functions [1,2]. Cultivated cropland accounts for approximately 12% of the Earth's non-ice-covered land surface and provides indispensable survival supplements (e.g., food and fiber) for human beings [3,4].…”
Section: Introductionmentioning
confidence: 99%